An honest woman not just tomorrow, but forever: An analysis of Brazilian legislative process dealing with sexual crimes from the standpoint of the labelling approach - Jéssica Moraes Cesarino; Sergio Nojiri (Rivista di Criminologia, Vittimologia e Sicurezza)
Using the questions proposed by the criminological theory of the labelling theory, we propose to investigate the legislative processes that modified the criminal types of Title VI of the Brazilian Penal Code on crimes against sexual dignity, as well as the behavior of the agents behind the creation of the laws (deputies and senators), the investigation (police officers) and the trial (magistrates). To this end, we gave a brief overview of the labelling theory. Afterwards, we dealt with the legislative movements and institutional dialogues that removed the term “honest woman” and terms alluding to female virginity to increase protection and mitigate the stigmatization of people who have suffered sexual violence. Finally, we consider the consequences of Brazilian laws in cases of sexual violence. We noticed that despite the various legislative changes, the moral logic contained in the Explanatory Memorandum of the Brazilian Penal Code of 1940 remains: sexual crimes are offenses against honor, the honesty of families and public decency, and the offense against women's sexual dignity is relegated to the background.